Islamic, accounting and finance: challenges and opportunities in the new decade - Mohd. Alwi, Norhayati; Nelson, Sherliza Puat (s.n, 2012)
The papers that have passed the first level review were then sent for a second blind review process in order to add more credibility to this edited book. Majority of our paper reviewers are expert in their area and their opinions are mostly sought after. At the end of the thorough review and editing process, we arrived to eleven chapters altogether. The title of this book; Islam, Accounting and Finance: Challenges and Opportunities in the New Decade, as a preference to show our utmost appreciation to all parties who have worked hard for the conference.